The quest for identity of African American women from 1939 to 2000 in postmodern American Drama - Obaid, Ismael Hasan (2020)
This study was conducted to explore the oppression of African American women as well as to determine how their identity was in a struggle to gain in a selection of Postmodern American plays. Sharing the experiences of African American women and their black community of that time, represented as a journey towards black femininity on a stage. The significance of this study was derived from the broad topic of womanhood because the issue of black women with identity is relevant to a variety of fields. This study made use of Martin and White's (2005) account of Appraisal Theory. By utilizing one of the Systemic Functional Linguistics systems; (interpersonal metafunctions), as a framework and focus completely on all the appraisal categories gave the readers a new way of understanding those literary texts. This approach aims to investigate the selected data sets to obtain an insight into the evaluative discourse of women with regard to their emotional, evaluative, and judgmental stances in their speaking. The study used four Postmodern American plays which were; Lorraine Hansberry's “A Raisin in The Sun”, 1959, Adrienne Kennedy's “The Funnyhouse of a Negro”, 1964, Ntozake Shange's “For Colored Girls Who Have Considered Suicide /When the Rainbow is Enuf”,1976, and finally, Suzan-Lori Parks' “In the Blood”, 1999. All the selected plays were written between 1939 to 2000 to trace back the status of African American women and the main factors which helped them to overcome their identity issue. It is concluded that African American women have been doubled marginalized and discriminated because of their skin colour as well as their gender. And later on, through the timeline of the current study, this issue had not been overcome completely. African American woman did not gain absolute freedom, complete individual identity, and citizenship within the scope of the assigned data sets. In other words, all of which ended with these women received some and not all of their self-appreciation and self-realization of who they were.